In-situ water quality assessment at recretional lake by using grab sampling technique - Sunar, N.M.; Hamdan, R.; Khalid, Amir; Zaidi, E.; Azhar, A.T.S.; Ali, R.; Hamid, H. A.; Hamidon, Nuramidah; Harun, H.; Muhamad, Mimi Suliza (Penerbit Uthm, 2018)
Sampling surface water sample are taken from rivers, lakes and similar surface waters. The simplest, a “grab” sample is taken at a selected location, depth and time. Normally, the quantity of water taken is sufficient for all the physical and chemical analyses that conducted on the sample. Sometimes, if the sampler is small, many analyses are necessary. Such as two grab samples collected at the station and then mixed in the same transport container.